Safety and efficacy of vitamin B(2) (riboflavin) produced by Ashbya gossypii DSM 23096 for all animal species based on a dossier submitted by BASF SE - Rychen, Guido (John Wiley and Sons Inc., 2018)

(untitled) (EFSA J)
The European Commission asked EFSA for an opinion on the safety for the target animals, consumer, user and the environment and on the efficacy of a riboflavin‐based additive (minimum 80%) produced by a genetically modified strain of Ashbya gossypii (DSM 23096). It is intended to be used in feed for all animal species and categories. The additive under assessment does not give rise to safety concerns on the genetic modification of the production strain. The additive contains 80% of riboflavin (vitamin B(2)) and 20% of spent growth medium. The additive is safe for target animals with a wide margin of safety. The use of riboflavin 80% produced by A. gossypii DSM 23096 in animal nutrition does not represent a safety concern for consumers. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) cannot draw a final conclusion on the risk posed for the user by inhalation of riboflavin produced by A. gossypii DSM 23096 and on the potential to be irritant to skin or eyes. The product under assessment is not a skin sensitiser; however, riboflavin is a known photosensitiser. The use of riboflavin produced by A. gossypii DSM 23096 in animal nutrition does not pose a risk to the environment. The additive is regarded as an effective source of riboflavin in covering the animal's requirement when administered via feed. The FEEDAP Panel made recommendations on the description of the additive.